Peta Gerakan Islam Radikal Kontemporer Di Indonesia - Rijal Mumazziq Z (STAIFAS-Press, 2020)
In the last two decades, the radical Islamic movement in Indonesia has flourished. Starting from solidarity with the slumped Islamic world, returning to the teachings of the Koran and hadith, rejection of Western domination of a Muslim state, to inflating the spirit of jihad, and efforts to realize an